ECONOMIC EFFICIENCY IN USAGE OF BELARUSIAN BROWN COAL DEPOSITS - V. V. Kravchenko (Наука и техника)
Methodology for economic evaluation of the effective use of the Belarusian brown coal deposits has been developed on the basis of systematic analysis of scientific, statistical and economic data. The obtained methodology allows to perform multi-variant optimization calculations under various uncertainty level without reduction to the same energy effect that is especially important while developing economic forecasts and programs for the long term perspective. Using this methodology evaluation of various directions pertaining to usage of the Belarusian brown coal has been done and recommendations on their possible application have been given in the paper.